Methane production and energy balance in crossbred male calves fed on rations containing different ratios of green sorghum and wheat straw - HAQUE, N; SARASWAT, M L; SAHOO, A (The Indian Journal of Animal Sciences, 2014)
Growing crossbred (Holstein FriesianxHariana) male calves (8) weighing 225kg were divided into 2 groups of 4 each to study the methane production and energy bal;mce in crossbred calves fed on diets having 2 different ratios of wheat straw and sorghum. Green sorghum and wheat straw were in the ratio of 90: 10 in group 1 and 60:40 in group 2. Both the rations were supplemented with wheat bran. The dry matter intake was 93.9±4.49 and 95.5±8.33 g/kg W0.75/d in groups 1 and 2 respectively. The digestibility of DM, OM, CP and NFE were significantly (P<0.05) higher in group 1 than that in group 2. The GE, DE and ME intake was similar in both the groups. However, digestibility and metabolizability of GE was significantly higher in group 1. Methane energy loss (Mcal/d, kcal/kg W0.75/d, % GE and % DE) was significantly lower in group 1 than in group 2. Methane production litres/kg digested OM was lower in group 1 (31.3±2.31) than that in group 2 (46.9±3.31). Energy balance was 106.5±16.05 and 70.0±26.18 kcal/kg W0.75/d in groups 1 and 2, respectively, which did not differ sigificantly. It is concluded that methane production is comparatively lower in growing crossbred calves fed higher level of green sorghum supplemented with wheat bran in the ration.